Criminology and the sociology of organizations: analogy, comparative social organization, and general theory - Vaughan, Diane (Crime, law and social change, 2002)
The sociology of organizations offers conceptual tools that can be used by criminologists. The logic of crossing intra-disciplinary boundaries to borrow conceptual tools rests in the analogical properties of structure and process across social settings that are fundamental aspects of all social organization. Analogy itself is underrecognized and used as a tool for conceptual thinking and analysis in sociology. In this article, I give examples of theories and concepts from the sociology of organizations that can usefully be applied to substantive criminological problems. Then I compare family violence and corporate crime as examples of organizational misconduct, foregrounding the organizational setting in order to examine links between micro-, meso-, and macro-levels of analysis. These two exercises demonstrate that incorporating organization theory into criminological research can provide new insights in data analysis of substantive problems, build toward general sociological theory, and toward integrative general criminological theory that escapes the levels of explanation problem.